Do tuition fees affect the mobility of university applicants? Evidence from a natural experiment - Nadja Dwenger; Johanna Storck; Katharina Wrohlich (Institute for the Study of Labor (IZA), 2009)
Several German states recently introduced tuition fees for university education. We investigate whether these tuition fees influence the mobility of university applicants. Based on administrative data of applicants for medical schools in Germany, we estimate the effect of tuition fees on the probability of applying for a university in the home state. We find a small but significant reaction: The probability of applying for a university in the home state falls by 2 percentage points (baseline: 69%) for high-school graduates who come from a state with tuition fees. Moreover, we find that students with lower high-school grades react more strongly to tuition fees. This might have important effects on the composition of students across states.
Keywords: I22; I28; H75; R23; 330; Mobility of high-school graduates; tuition fees; natural experiment; Studienfinanzierung; Studierende; Binnenwanderung; Teilstaat; Deutschland